Staking the Monster: A Politics of Remonstrance - Ingebretsen, Edward (Religion and American culture, 1998)
Monster, you are an abomination. I love you. Marquis de Sade, Juliette - Perversion is not an innate desire … but an identity and a category which is socially produced. Jeffrey Dollimore, Sexual Dissidence - Some years ago I asked in an examination paper … “why were heretics persecuted in the thirteenth Century?” The question was very popular and the answer, with great confidence and near unanimity, “because there were so many of them.” R. I. Moore, The Formation of a Persecuting Society - A social order reveals the limits of its imagination in two particular ways. The first is in the methods of fear by which it constructs the unspeakable (the “monstrous” or the “inhuman”) as symbolic center of social energy. The second is in the means, legal and extralegal, then used to repudiate and silence that energy.